Beliefs and practices of Indonesian mothers and health workers about diarrhea among pre-school children in Bandung, Jawa Barat - Damayanti, Didit
The study was conducted in the Bandung district, West Java, Indonesia. The objectives of the study were to describe the beliefs and practices of mothers about diarrhea, assess the scientific basis and determine the influence of education, income and household size on the mothers' beliefs and practices. It also attempted to describe the beliefs of health workers, analyze the scientific basis of these beliefs and determine the influence of type of work, length of employment and training program on their beliefs about diarrhea. A total of 383 mothers and 107 health workers participated as respondents of the study. The questionnaire for mothers and health workers sought to obtain information about their beliefs in such matters as causes of diarrhea., signs and pathology, treatment and prevention. In addition, another questionnaire was asked to find out the practice of mothers in managing their children when the latter have diarrhea. The beliefs of both groups of respondents were assessed based on scientific information. The higher the score, the more correct or scientifically sound the beliefs are. The practices of mothers were similarly scored. The results showed that majority of the mothers had fair to good belief scores. However when it came to practice, majority got poor scores. There was no significant correlation between the mothers' belief scores and their practices scores. Of the three socio-economic variables considered, educational attainment of the mothers appeared to be the more highly correlated to belief scores. In this study, the most common relationship between belief and practice of mothers about diarrhea was that positive belief is accompanied by positive practice. In the area of practice, medicine continues to play an important role as the first step or even a single practice in diarrhea treatment, even more than the use of home remedy or ORS and SSS. As to the health workers, diarrhea-focused training programs appeared more effective than general training programs where diarrhea is only one topic. The health workers had a significantly higher belief scores compared to mothers, and among the health workers, medics and paramedics had higher belief scores compared to Cadres and administration personnel in the health center.